Identification of Machine Tool Defects Using Laser Interferometer - Matus, Miroslav; Bechny, Vladimir; Joch, Richard; Drbul, Mario; Czan, Andrej; Sajgalik, Michal (Manufacturing Technology Journal, 2024)
The geometric accuracy of a machine is primarily determined by the accuracy of assembly, manufactur-ing, and overall setup. Standardized procedures for assessing geometric accuracy are established and detailed in delivery protocols for various types of machining machines. To effectively monitor and ana-lyze machining machine errors, the most suitable approach is to construct a comprehensive error balance that accounts for the overall performance of the machine. This error balance methodology, a tool within the realm of system analysis, is utilized for predicting and managing systemic errors. The errors ob-served in machined components are intimately connected to the errors present in the machining ma-chines themselves. These errors are further intertwined with the design and physical properties of indi-vidual machine components, as well as their interactions. In the case of multi-axis machines, they col-lectively determine the overall accuracy of the produced components. The objective of this study is to analyze machining machine errors using the Renishaw XL-80 laser interferometric system. The findings of this study reveal that errors in machining machines can also be the result of the dynamics of the cut-ting process, which may have a significant impact on accuracy.
Keywords: Diagnostics; Machining Machines; Laser Interferometry; Machining Machine Errors